2022
DOI: 10.1371/journal.pone.0265458
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the impact of coronavirus disease 19 on hospitalization rates for chronic non-communicable diseases in Brazil

Abstract: Background The coronavirus disease (COVID-19) pandemic has impacted health services and healthcare systems worldwide. Studies have shown that hospital admissions for causes related to chronic non-communicable diseases (NCDs) have decreased significantly during peak pandemic periods. An analysis of the impact of the COVID-19 pandemic on hospital admissions for NCDs is essential to implement disability and mortality mitigation strategies for these groups. Therefore, this study aimed to analyze the impact of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 36 publications
1
14
0
4
Order By: Relevance
“…Moreover, reductions in hospitalization rates might occur due to several factors (34). In 2020 and 2021, however, these factors were compounded by the effect of the pandemic caused by the novel coronavirus (34). In Brazil, the entire healthcare system was impacted, not only by the demand for care of COVID-19 cases, but also by the isolation and social distancing measures that compromised people’s access to healthcare services (34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, reductions in hospitalization rates might occur due to several factors (34). In 2020 and 2021, however, these factors were compounded by the effect of the pandemic caused by the novel coronavirus (34). In Brazil, the entire healthcare system was impacted, not only by the demand for care of COVID-19 cases, but also by the isolation and social distancing measures that compromised people’s access to healthcare services (34).…”
Section: Discussionmentioning
confidence: 99%
“…In 2020 and 2021, however, these factors were compounded by the effect of the pandemic caused by the novel coronavirus (34). In Brazil, the entire healthcare system was impacted, not only by the demand for care of COVID-19 cases, but also by the isolation and social distancing measures that compromised people’s access to healthcare services (34). In this study, we identified a reduction in hospitalization rates for both wtATTR-CM and hATTR-CM cohorts, probably related to the isolation and social distancing arising from COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…The weekly number of admissions and consultations, in the pandemic and pre-pandemic groups, was estimated using a negative binomial regression model, in line with other studies [11][12][13][14][15][16]. To adjust for the two pandemic waves, in spring and fall/winter, we used a three-basis spline model with an interaction term with the pandemic and pre-pandemic group.…”
Section: Methodsmentioning
confidence: 99%
“…From Brazil, Guimarães et al . [12] reported a 27% drop in hospital admissions for NCDs after the onset of the pandemic. Similarly, from Italy, Caminiti et al .…”
Section: Disrupted Healthcare Servicesmentioning
confidence: 99%
“…Ayele et al [11] reported from North Western Ethiopia that poor treatment control increased significantly in ambulatory patients with hypertension and diabetes from around 25% prior to the COVID-19 pandemic to 35% 4 months following the date of the first COVID-19 case detection. From Brazil, Guimarães et al [12] reported a 27% drop in hospital admissions for NCDs after the onset of the pandemic. Similarly, from Italy, Caminiti et al [13] reported that admissions for NCDs dropped by approximately one third during the COVID-19.…”
Section: Disrupted Healthcare Servicesmentioning
confidence: 99%